Regularization Method of Restoration of Input Signals of Nonlinear Dynamic Objects that Determined by Integro-Power Volterra Series - Ponedilok, V.V. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2018)
The article offers a regularization method for solving the polynomial integral Volterra equations of the first kind while solving the problem of restoration of the input signal of a nonlinear dynamic object determined by the integro-power Volterra series. The use of integro-power Volterra series makes it possible to simplify the primary nonlinear mathematical models of nonlinear dynamic objects turning them into quasi-linear ones. Polynomial Volterra equations of the first kind are solved by introducing the additional differential regularization operator. It is offered to solve the obtained integrodifferential equations using quadrature algorithms by iterative methods. У статті пропонується регуляризаційний метод розв’язування поліноміальних інтегральних рівнянь Вольтерри І-го роду при розв’язуванні задачі відновлення вхідного сигналу нелінійного динамічного об’єкта, що поданий інтегро-степеневим рядом Вольтерри. Застосування інтегро-степеневих рядів Вольтерри дає змогу спростити первинні нелінійні математичні моделі нелінійних динамічних об’єктів перетворивши їх до квазілінійного вигляду. Розв’язування поліноміальних інтегральних рівнянь Вольтерри І-го роду здійснюється шляхом введення додаткового диференціального регуляризаційного оператора. Отримані інтегродиференціальні рівняння пропонується розв’язувати за допомогою квадратурних алгоритмів шляхом використання ітераційних методів.